Values and basic beliefs of working and non-working students - N. A. Tsvetkova; K. E. Lagvilava (Вестник университета, 2022)
The article is prepared on the basis of empirical data obtained from a sample of senior students divided into two groups – a group of working and a group of non-working students. They studied and compared social values and individual priorities, as well as basic beliefs. It is shown that both student samples are generally characterized by the same average overall level of social values (3.9 points out of 7 possible) and a low overall level of individual priorities, although it is higher for working students (2.1 vs. 1.8 points). The priority of social values over individual values was found in both groups. Intergroup differences in the value of “power” are established: its indicator is higher among working students; non-working students attach more importance to independence. Working students, in comparison with non-working students, have a higher individual significance of conformity and achievements. Students of both groups have a high level of conviction in their own worth and luck, but the world seems to them more unfair than fair. Significant intergroup differences in none of the five basic beliefs were revealed.